Computed Tomographic Evaluation of Pancreatitis and its Complications- Pictoral review - Ullal, S; Joshi, KS; Pant, P (Nepal Journal of Medical Sciences, 2012)
Pancreatitis is one of the commonest pancreatic pathology encountered in day to day clinical practice. Early detection of the entity and its complications can significantly reduce the mortality and morbidity. Various imaging modalities are now available including newer interventional techniques for the diagnosis and therapeutic interventions. For diagnostic purposes, Computed Tomography (CT) has long been regarded as one of the most efficient imaging modalities for evaluation of pancreatitis. This pictoral review is based on Helical CT scans performed in total 50 patients suspicious of having pancreatitis in Kasturba Medical College Hospital, Attavara, Mangalore, India between 2008-2009 and Dhulikhel Hospital, Dhulikhel, Nepal 2010. Various morphological features of both acute and chronic pancreatitis were found on helical CT abdomen. The CT features of acute pancreatitis were focal or diffuse enlargement of pancreas, areas of necrosis, peripancreatic fat strandings, extrapancreatic fluid collections, perinephric fat stranding, perirenal fascial thickening, ascites, pleural effusion, pseudocyst formation etc. The CT features of chronic pancreatitis were focal or diffuse atrophy of the gland, duct dilatation, pancreatic calcifications, ductal calculi etc. Various complications encountered were acute fluid collections, pseudocyst formation, necrosis, pseudoaneurysm, portal vein thrombosis, abscess formation etc. DOI: http://dx.doi.org/10.3126/njms.v1i2.6613 Nepal Journal of Medical Sciences. 2012;1(2): 123-31